Pengembangan Sistem Manajemen Pengetahuan Kawitan Melalui Pendekatan Ontolgi - Diani, I Dewa Ayu; Suhartana, I Ketut Gede; Kadyanan, I Gusti Agung Gede Arya; Karyawati, Anak Agung Istri Ngurah Eka (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2025)
The rapid advancement of technology and modernization in Bali has significantly impacted on the preservation of local culture, one of which is the Kawitan tradition. Kawitan is a kinship system that holds a crucial role in the social structure of Balinese Hindu society, but its existence is increasingly threatened due to the lack of accessible documentation and the declining interest among younger generations to explore their ancestral origins. This study aims to develop a web-based knowledge management system about Kawitan using an ontological approach to preserve and disseminate information related to Kawitan genealogy. The ontology development method employed is Methontology, implemented using Apache Jena Fuseki as the triple store, while the system interface is developed with Laravel and Tailwind CSS. The system includes features such as statistics, genealogical search, and search for inter-family relationships. The outcome of this development is expected to bridge the information gap and raise awareness among the younger generation regarding the significance of understanding their Kawitan as a part of preserving Balinese cultural heritage.